PENERAPAN MEDIA KUIS INTERAKTIF KAHOOT UNTUK MENINGKATKAN SPEAKING SKILL DI DESA SUBANG - Anita Anggraeni; Cynantia Rachmijati; Dewi Listia Apriliyanti (Abdimas Siliwangi, 2020)
Characteristics compared to those who are more mature. They generally have a high curiosity but low attention span therefore different learning methods and techniques are needed. With the development of technology, more technology-based learning techniques are being implemented. The level of education in Desa Jalancagak Subang, which is still uneven, requires refreshing learning methods, especially related to learning English. Community service entitled "Application of Kahoot interactive quiz media to improve students speaking skill in Subang village” aims to provide insight into the knowledge of teachers related to Kahoot learning media and image media which are expected to help develop students' creativity and speaking skills and skills add to the nuances of teaching activities both conventionally and more modern.